The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jpainsymman.2015.12.329
|View full text |Cite
|
Sign up to set email alerts
|

From “Breakthrough” to “Episodic” Cancer Pain? A European Association for Palliative Care Research Network Expert Delphi Survey Toward a Common Terminology and Classification of Transient Cancer Pain Exacerbations

Abstract: Context. Cancer pain can appear with spikes of higher intensity. Breakthrough cancer pain (BTCP) is the most common term for the transient exacerbations of pain, but the ability of the nomenclature to capture relevant pain variations and give treatment guidance is questionable.Objectives. To reach consensus on definitions, terminology, and sub classification of transient cancer pain exacerbations. Methods.The most frequent authors on BTCP literature were identified using the same search strategy as in a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 29 publications
(30 reference statements)
1
60
0
2
Order By: Relevance
“…Some patients, for example, avoid taking a medication because BTP intensity is not considered high enough. On the other hand, in a recent Delphi survey, experts in the field of BTP suggested that transient pain exacerbations can occur independently of background pain level and ongoing pain medication, and the phenomenon includes several subgroups of BTP types [8]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some patients, for example, avoid taking a medication because BTP intensity is not considered high enough. On the other hand, in a recent Delphi survey, experts in the field of BTP suggested that transient pain exacerbations can occur independently of background pain level and ongoing pain medication, and the phenomenon includes several subgroups of BTP types [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported satisfaction with pain treatment is an important outcome measure when assessing both background pain and BTP [8]. Of interest, the use of FPNS and IV-M, home care assessment, pain therapy setting, and the absence of anticancer treatment were associated with the highest level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, patients may have short-lived episodes of pain without the existence of background pain 45. Recently, it has been suggested that short-lived episodes of pain that do not fit the diagnostic criteria for BTcP should be called ‘episodic pain’,46 even though (paradoxically) episodic pain has been used as a substitute term for BTcP in the past 22 47…”
Section: Comparison Of Recommendationsmentioning
confidence: 99%